Making investment decisions : a look at the performance of the industrial and commercial sector in the Singapore market. - Chua, Wan Ping. (2013)
This report presents the findings of our empirical study on the performance of 16 selected Industrial and Commercial stocks on the Singapore Stock Exchange.